Immunosuppression for ipilimumab-related toxicity can cause pneumocystis pneumonia but spare antitumor immune control - Arriola, Edurne (Oncoimmunology, 2015)
Ipilimumab is a standard therapy for advanced melanoma. Severe immune related adverse events occur in up to 30% of patients and require treatment with immunosuppressants such as steroids or the anti-TNFα antibody, infliximab. We describe two patients with advanced melanoma treated with ipilimumab. Both suffered from severe immune related side effects and required prolonged immunosuppression with steroids and/or infliximab. Both patients recovered and in spite of the immune suppression, demonstrate clinical evidence of tumor control. This argues that distinct immunological effector functions control nosocomial infection and tumor, respectively. To our knowledge, these are also the first two case reports of pneumocystis pneumonia in this setting.